2008
DOI: 10.4049/jimmunol.180.11.7537
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania braziliensis Infection Induces Dendritic Cell Activation, ISG15 Transcription, and the Generation of Protective Immune Responses

Abstract: Leishmania (Viannia) braziliensis is the causative agent of cutaneous and mucosal leishmaniasis in South America, and the latter is a severe and disfiguring form of the disease. Our understanding of how L. braziliensis parasites interact with dendritic cells (DCs) is limited, partially due to the difficulty in generating axenic amastigotes. In this study, we successfully generated axenic amastigotes of L. braziliensis and used them to test the hypothesis that L. braziliensis infection efficiently triggers inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 52 publications
(60 reference statements)
4
75
0
1
Order By: Relevance
“…However, DC-NK cell cocultures did not further enhance DC or NK cell activation. Nevertheless, comparative studies with two developmental stages of L. amazonensis and L. braziliensis parasites confirmed our previous findings (42) and suggested to us that the lack of infectionmediated DC and NK cell activation was unique to L. amazonensis amastigotes.…”
Section: Cd40supporting
confidence: 71%
See 3 more Smart Citations
“…However, DC-NK cell cocultures did not further enhance DC or NK cell activation. Nevertheless, comparative studies with two developmental stages of L. amazonensis and L. braziliensis parasites confirmed our previous findings (42) and suggested to us that the lack of infectionmediated DC and NK cell activation was unique to L. amazonensis amastigotes.…”
Section: Cd40supporting
confidence: 71%
“…Axenic L. amazonensis amastigotes (strain LV78; obtained from Kwang-Poo Chang, Department of Microbiology and Immunology, Chicago Medical School) were maintained routinely in complete Grace's medium at 33°C (15). L. braziliensis amastigotes (LC1418) were freshly transformed from low-passage-number promastigotes and cultured in complete Grace's medium at 33°C and 5% CO 2 (42). To prepare heat-killed parasites, we incubated amastigotes (8 ϫ 10 7 /ml in phosphate-buffered saline [PBS]) in a 60°C water bath for 15 min, as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on their maturation state, DCs have the ability to polarize distinct T cell subsets, such as T helper cells, regulatory T cells and cytotoxic T cells, controlling the outcome of infections due to pathogenic microorganisms. Several studies have demonstrated that DCs can be infected by Leishmania parasites but with conflicting results regarding the regulatory role of DCs in parasite growth and host susceptibility (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%